Perspective parents toward students diversity in inclusive education elementary school - Mumpuniarti Mumpuniarti; C. Asri Budiningsih; Dinar Westri Andini; Ayu Rahayu (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
The perspective of parents who support student diversity in school will open to a variety of different problems. The attitude is expected to encourage the implementation of integration and harmony among diversity. Therefore, the objective of the study was to describe the views of parents towards student diversity in inclusive education. Diversity from the perspective of parents determines the attitude of agree and disagree, as well as the right view of inclusive. The research method used a questionnaire to respondents of 99 parents from elementary schools in five regencies of the Special Region of Yogyakarta. The results showed that the majority of parents still had a narrow understanding that the concept of inclusive was the same with Student Educational Need (SEN). Here, the concept of labeling might understand as a misconception phenomenon. However, the majority of parents agreed to the SEN in regular schools, but an understanding of separate learning is the responsibility of the special supervisor or, interpreted as the inclusion officer. The implications need the education to understand the inclusion correctly and discuss the perspectives of parents to contribute to the success of learning in inclusive elementary schools.